Managing the primary school - Dean, Joan (Educational management series., 2002)
This new edition of Managing the Primary School brings up-to-date the consideration of the tasks and skills of the headteacher which was a feature of the first edition. Like the first edition, this book deals with all aspects of the headteacher's role, including a discussion of the changing relationships with parents and governors, and an examination of the headteacher's involvement with marketing the school and controlling its finances. Each chapter looks at a particular group of skills and tasks which are a part of the management role. Joan Dean takes into account the implication.